Antaraksi Fisik Padatan Pada Kombinasi Senyawa Aprobarbital dan Isopropilantipirina - Sundani Nurono (Institut Teknologi Bandung, 1999)
The influence of mechanical and thermal energy to the physical mixture of (1:9), (3:7), (1:1), (7:3) and (9:1) of two drugs namely aprobarbital and isopropylantipyrin as representative model of sedative and analgetic-antipyretic groups has been carried out. In fact, both of those substances could part of physically interact to form a molecular compound. Such compound has two eutectic points at 96oC and 123oC, each. Whilst the melting point of the formed molecular compound is 129oC (Thermal analysis method). The molecular compound formation between aprobarbital and isopropylantipyrin was proved by crystallography methods i.e. diffractogram produced by x-ray diffraction, contact methode, thermal analysis (DSC) and microphoto of scanning electron microscope.